Advances in the design of cell-permeable fluorescent probes for applications in live cell imaging. Issue 97 (19th November 2018) - Alamudi, Samira Husen; Chang, Young-Tae
Abstract : Advances in the design strategy of cell-permeable small fluorescent probes are discussed. Their applications in imaging specific cell types and intracellular bioanalytes, as well as the cellular environment in live conditions, are presented. Abstract : Small fluorescent molecules have been an important tool for fluorescence-based imaging, thanks to their technical simplicity, sensitivity and structural flexibility. However, probing specific intracellular systems with a small fluorescent molecule is not an easy task owing to the intricate nature of the cells. Ideal imaging probes should be highly permeable and be without background noise to allow undisrupted observations. These probes will unquestionably be more advantageous for interrogating intracellular architectures and dynamics without compromising the cellular integrity, and could therefore be applied for applications in the native cellular environment. This review will highlight the advances in design strategies for cell-permeable fluorescent probes through a diversity-oriented fluorescence library approach and rational design via computational-aided predictive models. Here, we discuss a series of cell-permeable probe applications for imaging specific cell types and intracellular biomolecules, as well as the cellular environment.